Diagnosis and Management of Gastroenteropathy Asssociated to Non-steroidal Anti-Inflammatory Drugs - Stella Ilone; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) is a group of drugs used to treat pain, inflammation, and fever. High consumption of NSAIDs associated with high gastrointestinal side effects. Common complaint from patients, which ranging from mild heartburn to the onset of gastrointestinal bleeding, often complicates the adequate administration of NSAIDs. Various methods have been developed to reduce the likelihood of gastroenteropathy complication. Early diagnosis, appropriate prompt treatment, as well as adequate monitoring will reduce morbidity and mortality from complications due to NSAIDs. This paper will discuss the diagnosis and management of gastro-enteropathy NSAID through approaching the underlying pathophysiology.